Ayurveda Conquers Tobacco De-addiction: A Case Series Demonstrating Complete Success - Vatsal Harajbhai Barad; Poorvi K. Vyas; S. N. Gupta (Journal of Ayurveda, 2025)
Introduction: Tobacco addiction, a chronic neurobehavioral disorder, is driven by nicotine’s activation of mesolimbic dopaminergic pathways, inducing cravings, irritability, and stress-exacerbated dependence, often intensified by betel quid. Chewing tobacco, prevalent globally with high use in India, particularly among youths, increases oral and esophageal cancer risks. Ayurveda attributes addiction to Vata and Pitta imbalances, with Ruksha and Chala qualities driving cravings, Ushna and Tikshna intensifying irritability, and Rajas and Tamas disrupting mental channels. This study evaluates an integrative Ayurvedic protocol for Mawa/tobacco cessation. Main Clinical Findings: Patients presented with oral lesions (leucoplakia, erythroplakia, and ulcers) and psychological symptoms, including severe cravings, irritability, and stress-driven Mawa use. Nicotine dependence ranged from moderate to very high, with elevated mood disturbance, tension, and depression. Diagnosis: Nicotine dependence was quantified using the Fagerström Test for Nicotine Dependence–Smokeless Tobacco, while mood and psychological distress were assessed through the Profile of Mood States, revealing marked neurobehavioral dysregulation. Interventions: A 60-day Ayurvedic regimen included Padamshik Krama (gradual withdrawal), Sattvavajaya Chikitsa, Shirodhara, and Haritaki quids with Akarkarabha Churna. Outcomes: Nicotine dependence significantly decreased (P < 0.0001), with eight of ten patients achieving near-zero dependence by day 45 or 60; two with high baseline dependence progressed slower. Mood disturbance reduced from 47.9 to −18.9 over 3 months (P = 0.0001), alleviating tension, depression, and withdrawal symptoms. Conclusion: This Ayurvedic protocol effectively reduces tobacco dependence through gradual withdrawal, psychotherapy, and neuroendocrine stabilization, offering a culturally adapted cessation approach. Randomized controlled trials are needed to confirm efficacy.